Application of Combined Superficial Femoral Artery Stenting and Deep Femoral Artery Profundoplasty in Chinese Patients With Lower Extremity Artery Disease - Chi, Guoqing; Ding, Mingchao (Frontiers in Surgery, 2021)
Objective: Lower extremity artery disease (LEAD) increases sharply with age and results in severe burden in individuals and in society. This study aimed to compare the efficiency of simple superficial femoral artery stenting (SFAS) and the hybrid operation, such as combined SFAS and deep femoral artery profundoplasty (DFAP), in the treatment of Chinese patients with LEAD, classified as Rutherford grades 3–5. Methods: There were 200 patients with LEAD classified as Rutherford grades 3–5 included in the simple SFAS group (n = 100) and the combined SFAS and DFAP group (n = 100). Results: All the patients had median age of 71 years, and there were 143 males (71.5%). Not only the increase rate of ankle brachial index (ABI), but also reduction rate of Rutherford grade, were significantly higher after surgery in the combined SFAS and DFAP group than in the simple SFAS group (P < 0.05 for all). The patency rate of patients in the combined SFAS and DFAP group was significantly higher than that of patients in the simple SFAS group during the follow-up (P < 0.05). Proportion of amputation and claudication distance <200 m had no significant difference between the two groups during the 2-year follow-up (P > 0.05 for all). Conclusion: This study demonstrated that, compared with SFAS, combined SFAS and DFAP improved not only the ABI and the Rutherford grade after surgery but also the patency rate during the follow-up in Chinese patients with LEAD. Hybrid operation has significant value in alleviating clinical symptoms after surgery, and, thereby, improving vascular prognosis in Chinese patients.